Summoning Gramsci in Latin America - Barbero, Juan Jorge (Revista de Humanidades de Valparaíso, 2017)
Moving to the discipline of political sociology, we will articulate certain contributions of the critical Argentine Marxists, Silvio Frondizi and José Aricó, whose primary writings spanned the decades of 1960s to the 1990s. As a hypothesis, we will consider that these contributions can be productively linked to the themes of the “translatability of scientific and philosophical languages” and of “constitutionalism”, referred to by Antonio Gramsci at different moments of his political-intellectual trajectory, but fundamentally in his already legendary Prison Notebooks. In the period from the Cuban Revolution of 1959 to the transitions to democracy in Latin America in the last decades of the 20th century, what Frondizi and Aricó have set out to develop is the full potential of the notion of popular sovereignty.